The influence of green trade openness, natural resources rent, institutional quality, and R&D investment on environmental sustainability in the OECD: testing the EKC and LCC hypotheses - Abdulateif A. Almulhim; Md Qamruzzaman; Abdullah A. Aljughaiman (Frontiers in Environmental Science, 2025)
IntroductionThis study examines the impact of green trade openness, natural resource rents, institutional quality, and R&D investment on environmental sustainability across OECD countries from 2007 to 2022, testing both the Environmental Kuznets Curve (EKC) and Load Capacity Curve (LCC) hypotheses.MethodsWe apply panel econometric techniques, including CS-ARDL and nonlinear NARDL models, alongside causality analysis, to assess bidirectional and asymmetric relationships among variables.ResultsGreen trade openness, institutional quality, and R&D investment significantly reduce CO2 emissions and enhance load capacity. Conversely, natural resource rents increase emissions and degrade sustainability metrics. The EKC hypothesis holds with an inverted-U shape, while the LCC demonstrates sustainability improvement beyond economic thresholds.DiscussionFindings stress the critical role of governance, innovation, and sustainable trade in ecological outcomes. Policy recommendations advocate reinvestment of resource rents into green innovation and strengthening of institutional frameworks to align economic and environmental goals.